PENGARUH STRES KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KELURAHAN SUDIROPRAJAN - Natalia Adolfia Lotu; Zandra Dwanita Widodo; Laksono Sumarto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
The purpose of this study was to determine that: (1) the effect of work stress on employee performance, (2) the effect of work motivation on employee performance, (3) the effect of work discipline on employee performance, (4) the effect of the three variables together on employee performance. This research is aquantitative research. Quantitative research is are search method used to examinea particular populationor sample by using a survey method sourced from employee data at the Sudiroprajan sub-district office. The conclusions of this study are: t test shows that work stress, work motivation, work discipline togetherhave a significant effect on employee performance. Determinant test shows 64.8% results, it can beconcluded that the ability of work stress variables, work motivation and discipline work by 64.8% inimproving employee performance. Job stress is the most dominant variable of the two variables that significantly affect employee performance variables.